An atypical Phytophthora sojae RxLR effector manipulates host vesicle trafficking to promote infection - Wang, Haonan; Guo, Baodian; Yang, Bo; Li, Haiyang; Xu, Yuanpeng; Zhu, Jinyi; Wang, Yan; Ye, Wenwu; Duan, Kaixuan; Zheng, Xiaobo; Wang, Yuanchao (PLoS pathogens, 2021)
In plants, the apoplast is a critical battlefield for plant-microbe interactions. Plants secrete defense-related proteins into the apoplast to ward off the invasion of pathogens. How microbial pathogens overcome plant apoplastic immunity remains largely unknown. In this study, we reported that an atypical RxLR effector PsAvh181 secreted by Phytophthora sojae , inhibits the secretion of plant defense-related apoplastic proteins. PsAvh181 localizes to plant plasma membrane and essential for P . sojae infection. By co-immunoprecipitation assay followed by liquid chromatography-tandem mass spectrometry analyses, we identified the soybean GmSNAP-1 as a candidate host target of PsAvh181. GmSNAP-1 encodes a soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein, which associates with GmNSF of the SNARE complex functioning in vesicle trafficking. PsAvh181 binds to GmSNAP-1 in vivo and in vitro . PsAvh181 interferes with the interaction between GmSNAP-1 and GmNSF, and blocks the secretion of apoplastic defense-related proteins, such as pathogenesis-related protein PR-1 and apoplastic proteases. Taken together, these data show that an atypical P . sojae RxLR effector suppresses host apoplastic immunity by manipulating the host SNARE complex to interfere with host vesicle trafficking pathway.